2016
DOI: 10.5603/kp.a2016.0062
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive endothelial function assessment using digital reactive hyperaemia correlates with three-dimensional intravascular ultrasound and virtual histology-derived plaque volume and plaque phenotype

Abstract: Background and aim To study relationships between endothelial dysfunction (ED) and coronary atherosclerosis derived from intravascular ultrasound (IVUS) and virtual histology (VH). Methods Endothelial dysfunction was examined by EndoPAT system (Itamar Medical) in 56 patients who underwent IVUS and VH (Volcano corp.). Reactive hyperaemia index (RHI) < 2 was used for definition of ED. IVUS sequences were divided into 5 mm-long non-overlapping and adjacent vessel segments. Plaque phenotype was determined for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Vasomotor tone and appropriate blood pressure are maintained by the vascular endothelium, which responds to shear stress generated by increased blood flow and stimulates vasodilation [1]. Vascular damage is caused and intensified by endothelial dysfunction, which induces chronic inflammation of the vasculature, followed by the development of atherosclerosis and cardiovascular disease [2][3][4][5][6]. The endothelium is composed of a monolayer of endothelial cells that function as an endocrine organ and a 0.2-2-μm-thick, negatively charged surface layer called the glycocalyx, which is a primary-functional barrier for endothelial cell protection [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasomotor tone and appropriate blood pressure are maintained by the vascular endothelium, which responds to shear stress generated by increased blood flow and stimulates vasodilation [1]. Vascular damage is caused and intensified by endothelial dysfunction, which induces chronic inflammation of the vasculature, followed by the development of atherosclerosis and cardiovascular disease [2][3][4][5][6]. The endothelium is composed of a monolayer of endothelial cells that function as an endocrine organ and a 0.2-2-μm-thick, negatively charged surface layer called the glycocalyx, which is a primary-functional barrier for endothelial cell protection [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The method to monitor the response of a conduit artery endothelium is flowmediated dilation (FMD) [9], and reactive hyperemia-peripheral arterial tonometry (RH-PAT) has been developed to assess endothelial function in the small arteries of the fingers [10]. These methods are thought to significantly predict the risks of cardiovascular and cerebrovascular events, including angina, myocardial infarction, ischemic stroke, cerebral infarction, acute coronary syndrome, and heart failure [2][3][4][5]. Recently, RH-PAT and FMD have been compared, and it was suggested that these two methodologies are not associated and reflect different aspects of cardiovascular risks.…”
Section: Introductionmentioning
confidence: 99%
“…Although the relationships between RHI and pathologic levels of coronary atherosclerosis have been studied, there are no reports of vascular endothelial function tests in cases of other inflammatory skin diseases or wound healing other than keloids. In addition, we did not study the relationship between the pathology of keloids, RHI, and the pathology of blood vessels; therefore, it is difficult to define the pathological levels of keloids and RHI.…”
Section: Discussionmentioning
confidence: 99%